Students' Perceptions of the Use Google Form in the Online Learning Process - Nina Irnisa Fauziyah; Vera Lutviya; Ariska Dwi Fatmasari; Lisa Inawati Inawati; Ima Isnaini Taufiqur Rohmah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Muhammadiyah Cirebon, 2022)
Online learning or e-learning is a way to deliver lessons from teachers to learners that take place remotely rather than in conventional classroom. One of the tool that use in online learning is google form. Teachers usually used it to assess students' abilities, taking the attendance, and surveys. This research aims to determine students' perception regarding the use of google form in online learning at semester 3 English Education Department of IKIP PGRI Bojonegoro. To find out students' perception regarding the use of google form in online learning this research use qualitative method to collect the data and using questionnaire as a research instrument. The research findings showed that students have a good perception towards the use of google form in online learning specifically for submitted assignments, filled in the attendance list, and surveys.